Numerical modeling of the 1964 Alaska tsunami in western Passage Canal and Whittier, Alaska - D. J. Nicolsky; E. N. Suleimani; R. A. Hansen (Natural Hazards and Earth System Sciences, 2010)
A numerical model of the wave dynamics in Passage Canal, Alaska during the Mw 9.2 megathrust earthquake is presented. During the earthquake, several types of waves were identified at the city of Whittier, located at the head of Passage Canal. The first wave is thought to have been a seiche, while the other two waves were probably triggered by submarine landslides. We model the seiche wave, landslide-generated tsunami, and tectonic tsunami in Passage Canal and compute inundation by each type of wave during the 1964 event. Modeled results are compared with eyewitness reports and an observed inundation line. Results of the numerical experiments let us identify where the submarine landslides might have occurred during the 1964 event. We identify regions at the head and along the northern shore of Passage Canal, where landslides triggered a wave that caused most of the damage in Whittier. An explanation of the fact that the 1964 tectonic tsunami in Whittier was unnoticed is presented as well. The simulated inundation by the seiche, landslide-generated tsunami, and tectonic tsunami can help to mitigate tsunami hazards and prepare Whittier for a potential tsunami.